2021
DOI: 10.5897/ijpc2020.0625
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between premarital counselling and marital success: Perceptions of married Christians in Ghana

Abstract: The period before marriage is extremely critical in determining the success of the marriage. The period allows would-be couples the opportunity to learn more about each other and make informed decisions regarding the marriage. Churches in Ghana have for some years now organized premarital counselling programmes to prepare would-be couples for the realities of marriage and family life. They have obliged members to go through this premarital counselling before the marriage is celebrated in the church. Reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The second hypothesis which stated that there is no statistically significant difference in marital satisfaction between male and female spouses was rejected. This finding is supported by Adjovie and Dabone [14], "who even though had reported a negative perception of the efficacy of premarital counselling, found a significant mean difference between male (M=1.24, SD=0.16) and female (M=1.19, SD=0.15) married Christians regarding their perception on the essence of premarital counselling in the marital satisfaction ecosystem".…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The second hypothesis which stated that there is no statistically significant difference in marital satisfaction between male and female spouses was rejected. This finding is supported by Adjovie and Dabone [14], "who even though had reported a negative perception of the efficacy of premarital counselling, found a significant mean difference between male (M=1.24, SD=0.16) and female (M=1.19, SD=0.15) married Christians regarding their perception on the essence of premarital counselling in the marital satisfaction ecosystem".…”
Section: Discussionmentioning
confidence: 62%
“…However, this particular finding seem to contradict Adjovie and Dabone [14], "who, reporting on a study using a Ghanaian sample, indicated that Christian married couples held a negative perception of the effectiveness of pre-marital counselling in the marital satisfaction paradigm".…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations